Pengaruh Online Customer Riview dan Rating Terhadap Minat Pembelian Online Shopee (Studi Kasus Pada Santri Putri Pondok Pesantren Salafiyah Syafi'iyah Seblak Jombang) - Desi Intan Komariyah (BIMA : Journal of Business and Innovation Management, 2022)
Research analysis of the influence of online customer reviews and ratings on the interest in online purchases shopee on the students of pondok Pesantren Salafiyah Syafi'iyah Seblak. The research method used is quantitative. Data collection was conducted by disseminating questionnaires on 60 respondens. The results of this study stated that online customer review and rating each had a significant positive effect on purchase interest judging by the results of the t test which stated the value of online variable thitung customer review 2,419 > ttabel of 1.6715 and signification value of 0.019 < 0.05 then the value of variable thitung rating of 13.792 > ttabel of 1.05 6715 and signification value of 0.000 < 0.05. Online customer review and rating together positively and significantly influenced the purchase interest judging by the f test result which stated the Fhicalc value of 94,405 > Ftabel of 3.16 and signification value of 0.000 < 0.05. The hypothesis in this study is acceptable, therefore online customer reviews and ratings are included in the important factors that influence the interest in purchasing.  Keywords: Online Customer Review; Rating and Purchase Interests